Information security essentials a guide for reporters, editors, and newsroom leaders - McGregor, Susan E. (Columbia University Press, 2021)
As technological and legal changes have hollowed out the protections that reporters and news organizations have depended upon for decades, information security concerns facing journalists as they report, produce, and disseminate the news have only intensified. From source prosecutions to physical attacks and online harassment, the last two decades have seen a dramatic increase in the risks faced by journalists at all levels even as the media industry confronts drastic cutbacks in budgets and staff. As a result, few professional or aspiring journalists have a comprehensive understanding of what is required to keep their sources, stories, colleagues, and reputations safe.This book is an essential guide to protecting news writers, sources, and organizations in the digital era. Susan E. McGregor provides a systematic understanding of the key technical, legal, and conceptual issues that anyone teaching, studying, or practicing journalism should know. Bringing together expert insights from both leading academics and security professionals who work at and with news organizations from BuzzFeed to the Associated Press, she lays out key principles and approaches for building information security into journalistic practice. McGregor draws on firsthand experience as a Wall Street Journal staffer, followed by a decade of researching, testing, and developing information security tools and practices. Filled with practical but evergreen advice that can enhance the security and efficacy of everything from daily beat reporting to long-term investigative projects, Information Security Essentials is a vital tool for journalists at all levels
Keywords: LANGUAGE ARTS & DISCIPLINES / Journalism; Attribution of news -- United States; Attribution of news; Confidential communication -- Press -- United States; Electronic surveillance -- Government policy -- United States; Journalism -- Political aspects -- United States -- History -- 21st century; Leaks (Disclosure of information) -- United States